Evaluation of peel bond strength between Plexiglas acrylic (PMMA) and maxillofacial silicone using three different primers - Tanveer, Waqas; Wonglamsam, Amornrat; Tancharoen, Salunya; Tirasriwat, Arunee; Srithavaj, Theerathavaj (Mahidol Dental Journal, 2020)
Objective: The bonding of maxillofacial silicone to acrylic resin is a critical issue when rehabilitating with implants retained maxillofacial prosthesis. The aim of this study was to evaluate 180˚ peel bond strength between prefabricated Plexiglas acrylic and maxillofacial silicone by using three different primers. Material and Methods: The peel bond strength between maxillofacial silicone, A-2186 and Plexiglas acrylic resin was assessed by using three different primers (A-306, A-304 and A-330G). Specimens were divided into 3 groups according to the specific primer. All specimens were fabricated within Aluminum mold and evaluation of peel bond strength was done by Universal testing machine. One way ANOVA and Tukey’s test were used to analyze data with significance level set at 0.05. Modes of bond failures were assessed by visual inspection and categorized into cohesive, mixed and adhesive failures. Results: There was significant impact of primers on bond strength between silicone A2186 and Plexiglas acrylic (p <0.05). The 180˚ peel bond strength ranged from 1.63 to 4.67N/mm among primers groups. The primer A-330 had the highest peel bond strength of 4.67N/mm among primers (p < 0.05). Cohesive failure was mainly found with primer A-330 while mixed and adhesive failures were predominantly seen in primer groups, A-306 and A-304 respectively. Conclusion: A-330 primer provided the highest 180˚ peel bond strength between prefabricated Plexiglas acrylic and silicone A-2186. Plexiglas acrylic might be used as an alternative material to conventional acrylic resin during fabrication of maxillofacial prosthesis.